2024
DOI: 10.3390/w16050718
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae-Mediated Biosorption for Effective Heavy Metals Removal from Wastewater: A Review

Dumisane Mahlangu,
Keletso Mphahlele,
Francesco De Paola
et al.

Abstract: Environmental contamination by heavy metals poses significant threats to terrestrial and aquatic ecosystems, necessitating the development of effective remediation strategies. Conventional methods for heavy metal removal exhibit limitations, including inadequate efficiency and elevated costs. In this context, microalgae have emerged as a promising bioremediation approach due to their robust metal-binding capabilities, specifically through biosorption. This review comprehensively examines the role of microalgae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 188 publications
0
4
0
Order By: Relevance
“…were as follows: The microalgae Chlorella spp. and Spirulina maxima present a metal absorption percentage greater than 90% [54], which causes these chemical species to not be detected in the process effluent by atomic absorption spectrometry. In a previous study by Gutierrez-Casiano et al [44] this effect was demonstrated.…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…were as follows: The microalgae Chlorella spp. and Spirulina maxima present a metal absorption percentage greater than 90% [54], which causes these chemical species to not be detected in the process effluent by atomic absorption spectrometry. In a previous study by Gutierrez-Casiano et al [44] this effect was demonstrated.…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…The selectivity coefficients and the intended applications of the final product determine which process is applied. The removal of metal ions from solutions has been extensively studied using CP [27][28][29], membranes [30][31][32][33][34][35], SA [36][37][38][39][40][41], and IX [42] processes.…”
Section: Sitementioning
confidence: 99%
“…However, several species are sensitive to toxicants; thus, various algae species are widely recommended for ecotoxicological assays to evaluate the toxicity of water contaminants or as bioindicators for water pollution [ 26 , 27 , 28 , 29 , 30 ]. Microalgae can be an effective tool during the removal of nutrients, heavy metals, and other pollutants from natural waterbodies and wastewaters [ 31 , 32 , 33 , 34 , 35 ]. Moreover, microalgae and cyanobacteria such as Chlorella vulgaris Beijerinck [ 36 ] and Arthorspira platensis Gomont (commercial name: Spirulina platensis ) [ 37 ] are consumed as food supplements as well [ 38 , 39 , 40 ], and they are used in various industrial activities, such as in aquaculture and during the production of pharmaceuticals, animal feed, and cosmetics [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%